Retaking the Philippines America's return to Corregidor and Bataan, October 1944-March 1945 - Breuer, William B. (New York : St. Martin's Press, 1986)
Chronicles the U.S. military campaign to recapture Manila, Corregidor and Bataan in the South Pacific.
Includes index.
Bibliography: p. 274-276.
77801
Keywords: World War, -- Campaigns -- Philippines. -- 1939-1945